A DYW‐protein knockout in Physcomitrella affects two closely spaced mitochondrial editing sites and causes a severe developmental phenotype. (10th September 2013) - Schallenberg‐Rüdinger, Mareike; Kindgren, Peter; Zehrmann, Anja; Small, Ian; Knoop, Volker
Summary RNA‐binding pentatricopeptide repeat (PPR) proteins carrying a carboxy‐terminal DYW domain similar to cytidine deaminases have been characterized as site‐specific factors for C‐to‐U RNA editing in plant organelles. Here we report that knockout of DYW‐PPR_65 in Physcomitrella patens causes a severe developmental phenotype in the moss and specifically affects two editing sites located 18 nucleotides apart on the mitochondrial ccmFC mRNA. Intriguingly, PPR_71, another DYW‐type PPR, had been identified previously as an editing factor specifically affecting only the downstream editing site, ccmFCeU122SF. The now characterized PPR_65 binds specifically only to the upstream target site, ccmFCeU103PS, in full agreement with a recent RNA‐recognition code for PPR arrays. The functional interference between the two editing events may be caused by a combination of three factors: (i) the destabilization of an RNA secondary structure interfering with PPR_71 binding by prior binding of PPR_65; (ii) the resulting upstream C–U conversion; or (iii) a direct interaction between the two DYW proteins. Indeed, we find the Physcomitrella DYW‐PPRs to interact in yeast‐two‐hybrid assays. The moss DYW‐PPRs also interact yet more strongly with MORF (Multiple Organellar RNA editing Factor)/RIP (RNA editing factor interacting proteins) proteins of Arabidopsis known to be general editing factors in flowering plants, although MORF homologues are entirely absent in the moss. Finally, we demonstrate binding of Physcomitrella DYW‐PPR_98, for which no KO lines could be raised, to its predicted target sequence upstream of editing site atp9eU92SL. Together with the functional characterization of DYW‐PPR_65, this completes the assignment of RNA editing factors to all editing sites in the Physcomitrella mitochondrial transcriptome.